(untitled) (TRIM. Tordesillas, revista de investigación multidisciplinar, 2020)
The understanding and rediscovery of the cultural heritage of humanity implies tracing initiation rituals, ancestral traditions and primitive instincts embodied in the literary tradition. Setting some study parameters capable of segregating and cataloging this collective imaginary is essential to understand and justify the evolution and construction of the story. Based on the premises of Gilbert Durand, Martín Jiménez develops a complex conceptual map to determine the narrative time and space linked to the regimes of the symbolic imagination; it is precisely these anthropological structures of the imaginary that we will identify in García Márquez’s story “El ahogado más hermoso del mundo”.